ESG, CYBER GOVERNANCE, OPERATIONAL RISK IN BANK RESILIENCE: EVIDENCE FROM INDONESIAN BANKS - Trisna Aminwara; Sudarso Kaderi Wiryono; Raden Aswin Rahadi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines how ESG and cyber governance relate to operational risk and bank resilience in Indonesia, with bank stability used as its measurable aspect. Using balanced panel data from 17 KBMI 3 and KBMI 4 banks during 2019–2024, the study applies Fixed Effects regression with robust standard errors and year dummy variables. ESG and cyber governance are measured using disclosure-based indexes from annual and sustainability reports. Bank stability is measured using the natural logarithm of the Z-score, while operational risk is measured by operational risk-weighted assets divided by total risk-weighted assets. The findings show that ESG has no significant direct relationship with bank stability or operational risk. Operational risk is positively related to bank stability, reflecting risk-weighted exposure and capital absorption rather than suggesting that operational failures improve stability. The main finding is that cyber governance negatively moderates the ESG–operational risk relationship, indicating that stronger cyber governance reduces the marginal operational risk association of ESG. Based on these findings, a KRI-Based ESG–Cyber Governance–Operational Risk Monitoring Framework is proposed.